2016
DOI: 10.3109/02770903.2015.1108440
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposures and family history of asthma

Abstract: Significantly more asthmatic children with immediate relatives with a history of asthma have a pet at home and experience STS exposure compared to children without relatives with a history of asthma, suggesting association between life style choices/environmental exposures and family history of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
16
1
2
Order By: Relevance
“…In addition, we showed that CSE preferably induces CD4+ T cells to differentiate into Th2 cells via DCs. Epidemiologic, laboratory, and clinical studies clearly demonstrate that cigarette smoking is an important risk factor in Th2-mediated diseases such as asthma [32]. The role of DC-mediated Th1 and Th2 immunity is regulated by many factors, including Ag type and dose, the expression level of costimulatory molecules [33], the existence of polarizing cytokines and other mediators, and the time of exposure to the presence of innate receptor stimulants [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that CSE preferably induces CD4+ T cells to differentiate into Th2 cells via DCs. Epidemiologic, laboratory, and clinical studies clearly demonstrate that cigarette smoking is an important risk factor in Th2-mediated diseases such as asthma [32]. The role of DC-mediated Th1 and Th2 immunity is regulated by many factors, including Ag type and dose, the expression level of costimulatory molecules [33], the existence of polarizing cytokines and other mediators, and the time of exposure to the presence of innate receptor stimulants [34].…”
Section: Discussionmentioning
confidence: 99%
“…The rates of asthma and allergies continue to grow [72,73,74], where a combination of factors have played a role in the increasing rates, including increased rates of diagnosis [75]. For asthma, there are some common findings among studies for causal and related factors, such as positive association of a child’s asthma outcome with atopy, parental atopy and asthma, indoor and outdoor pollution, and a negative association with living in a rural area [53,73,74,76,77,78].…”
Section: Approachmentioning
confidence: 99%
“…History of asthma in parents, siblings or grandparents was reported by Sheikh et al study in 575 (69.8%) patients including father (17.8%) and mother (26.5%) (Sheikh et al, 2016).…”
Section: Discussionmentioning
confidence: 93%